STRATEGI PASANGAN MAWARDI ALI DAN TGK. HUSAINI A WAHAB DALAM MEMENANGKAN PILKADA 2017 DI ACEH BESAR (Suatu penelitian di Kecamatan Krueng Barona Jaya) - susan tari rizki; Effendi Hasan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRACT Mawardi Ali and Tgk. Husaini A Wahab successfully became the winner in 2017 regional head election in Aceh Besar Region. According to the result count of the voting place by General Election Committee and Independent Election Committee of Aceh Besar Regency, it has achieved 100% from all total 802 voting place. The pair of Mawardi Ali and Tgk. Husaini A Wahab was excel in 18 sub-district. Krueng Barona Jaya is one of the voting place which was won by the pair of Mawardi Ali and Tgk. Husaini A Wahab with 57 % percentage or 3841 voice from 6736 the legal voice. This research was aimed to know the winning strategy of Mawardi Ali and Tgk. Husaini A Wahab and the factor which may influence the winning pair of Mawardi Ali and Tgk. Husaini A Wahab in regional head election in 2017 in Aceh Besar Region in Krueng Barona Jaya Sub-district. This research used qualitative method through field and library study analysis. The field study was conducted through interview, while the library data such as electronic and printed document, constitution, thesis, article, and journal which has correlation with this study. The research result shown politic strategy which was used by Mawardi Ali and Tgk Husaini A Wahab on 2017 regional head election in Aceh Besar Region was the political communication such as intensive communication to grow special impression in the society mind, next to build believe and public image of this pair campaign were political marketing, and the second was political lobby. Using political lobby this pair approach political parties in Aceh Besar who has seat both in parliament and small parties. In conclusion, this research is the society interest toward the head region and vice head region candidate winning strategy which might be often influenced by the vision and mission and also greatly influenced toward the background of the candidate which were nominated. In winning 2017 regional head election of Mawardi Ali and Tgk Husaini A Wahab using campaign method called ‘political marketing’ which is permanent concept which must be continually conducted by a political party or contestant in building believe and public image.Keywords : Strategy, Political Communication, Party and Coalition.